Somatostatin therapy of acute experimental pancreatitis. - Lankisch, P G (1977)
Because somatostatin (SRIF) reduces exocrine pancreatic secretion, its effect on acute pancreatitis was investigated in rats. Linear SRIF reduced serum amylase and lipase but had no effect on pancreatic necrosis, oedema, leucocyte infiltration, and enzyme content. The mortality rate was not reduced. These results do not recommend the use of SRIF in the treatment of acute pancreatitis.